Thermoresponsive amphiphilic star block copolymer photosensitizer: smart BTEX remover - Cho, Kie Yong; Choi, Jae-Woo; Lee, Sang-Hyup; Hwang, Seung Sang; Baek, Kyung-Youl (ROYAL SOC CHEMISTRY, 2013)
A well-defined PNIPAM-PS star block copolymer with a porphyrin core was synthesized by a reversible addition-fragmentation chain-transfer (RAFT) process, and was found to efficiently capture and decompose environmentally toxic organic materials such as benzene, toluene, ethylbenzene, and xylene (BTEX) in water under UV irradiation and was easily recycled by filtration after simple thermal treatment.